Constitutional functions and constitutional problems of international economic law : international and domestic foreign trade law and foreign trade policy in the United States, the European Community and Switzerland /: international and domestic foreign trade law and foreign trade policy in the United States, the European Community and Switzerland. (2018) - Unknown
No abstract available